Resilensi Nelayan Pesisir Selatan Takalar Dalam Menghadapi Perubahan Iklim: Studi Kasus di Desa Lagaruda, Kecamatan Sandrobone, Kabupaten Takalar - Abbas, Ria Renita Abbas; To Anwar, Sakaria; Firman , Firman; Yusri, Yusri; Sine, Arman Sine (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research discusses the ability of fishing communities on the South coast of Takalar to deal with climate change. The Lagaruda fishing community has important local knowledge in dealing with climate change, such as reading the seasons, reading the stars, and understanding the types of fish that appear. This knowledge helps them to reduce the risk of losing their jobs as fishermen and accidents in sailing. They also have the ability to make good use of natural resources and maximize the potential of natural resources to meet life needs. Knowledge of seasons, weather and fish species also helps them to manage risks and minimize the impact of climate change. Overall, the Lagaruda fishing community has resilience in facing climate change by using their local knowledge and natural resources.